Single-Cell Electrical Stimulation Using CMOS-Based High-Density Microelectrode Arrays - Ronchi, Silvia; Fiscella, Michele; Marchetti, Camilla; Viswam, Vijay; Müller, Jan; Frey, Urs; Hierlemann, Andreas (Frontiers in Neuroscience, 2019)
Non-invasive electrical stimulation can be used to study and control neural activity in the brain or to alleviate somatosensory dysfunctions. One intriguing prospect is to precisely stimulate individual targeted neurons. Here, we investigated single-neuron current and voltage stimulation in vitro using high-density microelectrode arrays featuring 26’400 bidirectional electrodes at a pitch of 17.5 µm and an electrode area of 5 × 9 µm². We determined optimal waveforms, amplitudes and durations for both stimulation modes. Owing to the high spatial resolution of our arrays and the close proximity of the electrodes to the respective neurons, we were able to stimulate the axon initial segments (AIS) with charges of less than 2 picoCoulombs. This resulted in minimal artifact production and reliable readout of stimulation efficiency directly at the soma of the stimulated cell. Stimulation signals as low as 70 mV or 100 nA,with pulse durations as short as 18 µs, yielded measurable action potential initiation and propagation. We found that the required stimulation signal amplitudes decreased with cell growth and development and that stimulation efficiency did not improve at higher electric fields generated by simultaneous multi-electrode stimulation.